2001
DOI: 10.1046/j.0022-0477.2001.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Seedling recruitment patterns over 4 years in an Australian perennial grassland community with different fire histories

Abstract: Summary1 Seedling recruitment was followed from 1993 to 1996 in four remnant Themeda triandra grassland sites in south-eastern Australia subjected to different long-term fire histories (1-, 2-, 4-year fire intervals, unburnt > 10 years). Multivariate analyses were used to separate the effects of site and year on recruitment and community dynamics. 2 Exotic species (mostly annual monocots such as Aira spp., Briza minor and Juncus capitatus ) dominated the seedling flora at all sites in all years. Seedlings of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…The poor representation of grasses in the seed bank (7-38%) contrasts with their dominance in the above-ground vegetation (75-81%). Similar observations were made by Morgan (2001), who found that seedlings of most native species in T. triandra grassland sites in Australia were rare despite their abundance in the standing flora. The absence of a persistent seed bank in South African grasslands highlights the importance of maintaining existing grasslands as a resource of seeds for restoration programmes.…”
Section: Discussionsupporting
confidence: 85%
“…The poor representation of grasses in the seed bank (7-38%) contrasts with their dominance in the above-ground vegetation (75-81%). Similar observations were made by Morgan (2001), who found that seedlings of most native species in T. triandra grassland sites in Australia were rare despite their abundance in the standing flora. The absence of a persistent seed bank in South African grasslands highlights the importance of maintaining existing grasslands as a resource of seeds for restoration programmes.…”
Section: Discussionsupporting
confidence: 85%
“…Establishment on disturbed soil mats did not significantly affect seedling mortality, at least for the short duration of this experiment. The effects may have been more pronounced, however, if mortality had been monitored over summer when soil moisture likely becomes more limiting to seedling growth (Morgan 2001). Several studies have indicated that differential long-term survival of herbaceous seedlings can be expected on microsites with soil crusts compared to bare ground areas (e.g.…”
Section: Speciesmentioning
confidence: 97%
“…In fire-prone ecosystems, fire is often followed by a flush of germination from the seed bank (Lemon, 1949;Keeley et al, 2003;Milberg and Lamont, 1995;Morgan, 2001). Seed banks in deciduous forest sites are generally small relative to those of other North American ecosystems (Harper, 1977), and typically include disturbance-oriented annual and perennial herb species (Matlack and Good, 1990;Hyatt and Casper, 2000;Schelling, 2006).…”
Section: Seed Germinationmentioning
confidence: 98%